Kontroversi Pelecehan Seksual Dalam Bentuk Merangkul Lawan Jenis - Fachri, Amanda Maharani; Az-Zahra, Fatimah; Azzahra, Khalita Putri; Dafa, M Naufal Abiyi; Najma, Siti Najla Nur; Yuli, Yuliana (Media Hukum Indonesia (MHI), 2024)
Sexual harassment is a serious issue that often causes controversy in various circles of society. One form of sexual harassment that is often discussed is the act of embracing someone of the opposite sex without consent. This research aims to examine the controversy surrounding the act of embracing the opposite sex in the context of sexual harassment. The methods used include literature reviews, case analysis. The research results show that the act of embracing someone of the opposite sex without consent may be considered sexual harassment depending on the local context and culture. Factors such as the perpetrator's intentions, the victim's reaction, and the social environment also influence the perception of the act. This study also reveals that there is an urgent need to increase awareness of physical boundaries and the importance of consent in interactions between individuals. In conclusion, a deeper understanding of the social and cultural context, as well as effective education, are essential to preventing sexual harassment in any form.